Drought models for the study of the vegetation moisture content; analysis of performance of different models in two mediterranean ecosystems for application in forest fire prevention - Bonora Laura; Vincenzi Matteo De (Central European Forestry Journal)
Vegetation water content is one of the most important parameters of vegetation status and health, and consequently a natural element that regulates several ecosystems worldwide; moreover, considering vegetation as fuel, this variable is related to wildfires. Forest fires and vegetation resistance to ignition during periods of drought are both strictly related to climate characteristics of the area. The contribution of this work is to evaluate the performance of vegetation drought models using field measured data (data related to local adaptation and phenotypic plasticity), data usually lacking. In the present work, moisture content of shrub vegetation and live foliage (fine fuels) were detected by field measurements of in Tuscany (Italy). In two plots of Quercus ilex L. and mixed broadleaves forest, seasonal and inter-annual variations of live fine fuels of several species are analyzed. The selected species constitute two sets (shrubs and trees) of vegetation typology characterized by a representative seasonal variability in mediterranean ecosystems. From nearby stations meteorological data were collected in each study area for the evaluation of fuel moisture indicators, including the Drought Code (DC) used in the Canadian Forest Fire Danger Rating System. The results of the present work have shown that for the summer season the slow response of live fine fuel moisture content (LFMC) to meteorological conditions (namely to precipitation), was well described by the DC. Empirical correlations between LFMC and DC for each species and site are proposed.